Single Strand Conformation Polymorphism analysis of PCR-amplified rDNA to differentiate medically important Aspergillus Species - K Diba; SH Mirhendi; P Kordbacheh; N Jalalizand (Tehran University of Medical Sciences, 2008)
"nBackground: Aspergillus species are associated with allergic bronchopulmonary disease, mycotic keratitis, otomycosis, nasal sinusitis and invasive infection. In this study, we developed a PCR-Single Strand Confomational Polymorphism method to identify the most common Aspergillus species and we showed some advantages of this method comparing a PCR-Restriction Fragment Length Polymorphism with our designed restriction enzyme. "nMethods: We selected ITS2, as a short fragment within the rDNA region (length size: 330 bp) to be amplified as small size PCR product. We mixed 5 ml of the PCR product with an equal volume of loading buffer and followed by incubation for 5 min at 95º C and quenching in an ice bath. The mixture was applied to a 6%-12% Gradient Poly acryl amide gel to run in a vertical electrophoresis, then gel was stained with ethidium bromide and silver nitrate which followed by an ethidium bromide staining. "nResults: Our results of restriction digestion showed a fine identification of 7 tested Aspergillus species during 5-6 hours after an overnight mycelial growth. As our results some of tested Aspergillus species: A. nidulans, A. fisheri, A. quadricincta, (A. fumigatus and A. niger) as a group and (A. flavus, A. tereus and A. ochraceus) as another group, can be discriminated. Moreover SSCP analysis enabled us to identify above Aspergillus species within 8-12 h after an over night growth without using an expensive restriction enzyme."nConclusion: It is concluded that Single Strand Conformational Polymorphism is a simple and rapid method for identification of some medically important Aspergillus.